To determine the psychometric properties of the General Oral Health Assessment Index (GOHAI) in a sample of adult rural dwellers in Southwestern Nigeria (2020)
This cross-sectional study was conducted among 395 adults attending dental outreach programs in Igboora, Nigeria. A translated interviewer administered questionnaire comprising socio demographic characteristics, GOHAI questions, self-rating of oral health and satisfaction with dental appearance was used to obtain data. Oral examination was also performed. The data obtained was analyzed for reliability and validity of GOHAI using SPSS and p value was set at <0.05%. The GOHAI score of respondents ranged from 5 to 60. Many 283 (71.6%) reported at least an impact of oral condition on quality of life (OHRQoL). The most reported impairment was the use of medication to relieve pain (221, 55.9%). GOHAI demonstrated excellent internal consistency with a Cronbach alpha of 0.97. Principal component analysis resulted in extraction of one factor; Kaiser-Meyer-Olkin measure was 0.96 and Bartlett’s test was significant (p<0.001). GOHAI was able to discriminate between those with periodontal treatment needs (p<0.001), missing teeth (p<0.001) or decayed teeth (p=0.001) and those without those oral findings. Higher GOHAI scores (less impact on OHRQoL) correlated negatively with poor selfrating of oral health (rs = -0.72, p<0.001) and dissatisfaction with dental appearance (rs = -0.70, p<0.001). More males (p=0.012) and divorced respondents (p=0.016) reported impacts on OHRQoL than others. GOHAI has acceptable psychometric properties and validity among underserved adults living in a rural Nigerian community